PENENTUAN SPESIES FORAMINIFERA BENTONIK KECIL DOMINAN PADA PERAIRAN SEMARANG, PROVINSI JAWA TENGAH - Nurani, Rina; Jurnaliah, Lia; -, Winantris (Bulletin of Scientific Contribution, 2014)
Twenty sea surface sediment samples are taken for research. Research area is located at Semarang Water and lied on 109º38’08,53’’ - 109º 43’31,57’’ BT and 05º 30’00’’ - 06º28’46,02’’ LS. Benthic foraminifera is marine unicellular animal that very useful to determine environment. The purpose of this research is to determine the genus of dominant small benthic foraminifera in order to interpret the environment. Based on quantitative method, result of the research shows total of genera is 29 with 145335 individual. Six genera which occur in all over samples are Ammonia, Anomalina, Asterorotalia, Elphidium, Heterolepa and Quinqueloculina. Genus Heterolepa is small benthic foraminifera dominant with total percentage individual is 35.957%. Based on the dominant genus, the environment of research area is marine (neritic).